The ancient magus' bride Volume 18 - Yamazaki, Kore; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2023)
Chise becomes a dragon and swims through the earth's ley lines to reach the Sargant family house, Elias and the others in tow. Together they make their way to Philomela, but she's too corrupted by the Testament to hear their words. To save her, Chise must delve into Philomela's inner world. What does she find there? "The people who want to help can reach out their hands."